Long-term outcomes of individuals with metabolic diseases identified through newborn screening - Mütze, Ulrike; Garbade, Sven; Gramer, Gwendolyn; Lindner, Martin; Freisinger, Peter; Grünert, Sarah; Hennermann, Julia; Ensenauer, Regina; Thimm, Eva; Zirnbauer, Judith; Leichsenring, Michael; Gleich, Florian; et al. (Pediatrics, 2020)
BACKGROUND: Although extended newborn screening (NBS) programs have been introduced more than 20 years ago, their impact on the long-term clinical outcome of individuals with inherited metabolic diseases (IMDs) is still rarely investigated. - METHODS: We studied the clinical outcomes of individuals with IMDs identified by NBS between 1999 and 2016 in a prospective multicenter observational study. - RESULTS: In total, 306 screened individuals with IMDs (115 with phenylketonuria and 191 with other IMDs with a lifelong risk for metabolic decompensation) were followed for a median time of 6.2 years. Although the risk for metabolic decompensation was disease-specific and NBS could not prevent decompensations in every individual at risk (n = 49), the majority did not develop permanent disease-specific signs (75.9%), showed normal development (95.6%) and normal cognitive outcome (87.7%; mean IQ: 100.4), and mostly attended regular kindergarten (95.2%) and primary school (95.2%). This demonstrates that not only individuals with phenylketonuria, serving as a benchmark, but also those with lifelong risk for metabolic decompensation had a favorable long-term outcome. High NBS process quality is the prerequisite of this favorable outcome. This is supported by 28 individuals presenting with first symptoms at a median age of 3.5 days before NBS results were available, by the absence of neonatal decompensations after the report of NBS results, and by the challenge of keeping relevant process parameters at a constantly high level. - CONCLUSIONS: NBS for IMDs, although not completely preventing clinical presentations in all individuals, can be considered a highly successful program of secondary prevention.
Gesehen am 14.01.2020